Alphabet reform in Kazakhstan: history and linguistic foundations - Yermukhamet Maralbek; Gulzar Oralbai (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article provides an overview of the alphabets used in Kazakhstan from the 5th century BCE to the present, tracing the history of Kazakh writing's formation, development, and transformation. It also offers insights and analysis on the specific linguistic steps of the national plan of transitioning to the Latin graphics. Although the transition to the Latin graphics is crucial for Kazakhstan's development and the future of the Kazakh language, it has faced significant delays since 1991 due to the complexity of the issue, which includes political-economic challenges and numerous linguistic hurdles. The current study examines Kazakhstan's modern alphabet reform from a linguistic perspective and explores the extralinguistic influences. It details the specific steps in the transition process, including the linguistic work conducted between 2017 and 2023, the five officially proposed Kazakh-Latin alphabet versions, and the corresponding spelling rules and orthographic dictionaries. The research also analyzes the theoretical issues, linguistic difficulties, and scholarly debates among Kazakh linguists regarding the transition to the new Kazakh alphabet based on Latin graphics. As a result of the study, the linguistic reasons for the delay in the process of Kazakhstan’s transition to the new Kazakh alphabet based on Latin graphics are identified, and certain conceptions are presented.